2012
DOI: 10.1111/j.1447-0756.2012.01855.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant supplementation in pregnant women with low antioxidant status

Abstract: Supplementation of women with low antioxidant status with micronutrients containing antioxidants during early gestation might reduce the risk of pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 34 publications
1
14
0
2
Order By: Relevance
“…Wibowo et al showed that supplementation of minerals with www. journals.viamedica.pl/ginekologia_polska antioxidant function, had a positive effect on the reduction of preeclampsia incidence during the initial stage of pregnancy in women not diagnosed with diabetes type 1 [31].…”
Section: Discussionmentioning
confidence: 99%
“…Wibowo et al showed that supplementation of minerals with www. journals.viamedica.pl/ginekologia_polska antioxidant function, had a positive effect on the reduction of preeclampsia incidence during the initial stage of pregnancy in women not diagnosed with diabetes type 1 [31].…”
Section: Discussionmentioning
confidence: 99%
“…In broad agreement with these findings, a randomised, placebo-controlled trial of 110 pregnant women (between 8-12 weeks gestation) who had low baseline antioxidant status were treated with either antioxidants or control diets daily until 2 weeks' postpartum. The study reported significant differences between the supplementation and control group for the incidence of pre-eclampsia (2.0% versus 14.5%) ,this study also found that mRNA levels of plasma SOD were significantly higher in the vitamin supplemented vs placebo supplemented women, providing evidence for a systemic antioxidant effect of these vitamins [41].…”
Section: Accepted Manuscriptmentioning
confidence: 67%
“…If we can detect FGR occurrence earlier, the patient developing FGR could be cared in an advanced medical center before onset and might reduce the risk of FGR by antioxidant supplementation like the preeclampsia prophylaxis we reported. 28 Of note, there were more missing values for the mRNA method than the protein method. We were able to replace some of the missing data by using an imputation method because we had longitudinal data.…”
Section: Discussionmentioning
confidence: 99%